2013
DOI: 10.1007/s12664-013-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of associated disorders in Indian patients with celiac disease

Abstract: Celiac disease (CD) is an immune-mediated disorder that may be associated with various diseases that share a similar pathogenic immune mechanism. This study reports on the prevalence of various diseases in a cohort of CD patients in northern India. Patients diagnosed with CD based on modified ESPGHAN criteria were prospectively evaluated for associated concomitant diseases. Of the 363 patients evaluated, 207 (57.0 %) were male. The mean age was 19 years. Seventy-one percent of patients presented with typical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Traditionally, CeD was thought to be uncommon in India; however, an increase in the number of cases had been recognized in late 1990 and 2000 onwards [11][12][13][14][15][16]. Three population-based studies, two from the northern parts of India and another multi-centric pan Indian study, showed that the overall prevalence of CeD in India is 0.67% and 1.2% in northern parts of India [17][18][19].…”
Section: Burden Of the Diseasementioning
confidence: 99%
“…Traditionally, CeD was thought to be uncommon in India; however, an increase in the number of cases had been recognized in late 1990 and 2000 onwards [11][12][13][14][15][16]. Three population-based studies, two from the northern parts of India and another multi-centric pan Indian study, showed that the overall prevalence of CeD in India is 0.67% and 1.2% in northern parts of India [17][18][19].…”
Section: Burden Of the Diseasementioning
confidence: 99%
“…Most of the subsequent reports on CD came from the northern part of India (States of Punjab, Haryana, Delhi, Rajasthan, Uttar Pradesh), where wheat is the staple dietary cereal [6,7,8,9,10,11,12,13,14,25,26,27,28]. …”
Section: Celiac Disease In Asiamentioning
confidence: 99%
“…Although there has been an increase in the number of publications on CD from the Asian region, there is a paucity of literature on its prevalence in most Asian nations, with the exception of India [6,7,8,9,10,11,12,13,14]. Additionally, few case reports and short reports are available from China, Pakistan and Japan [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Association of celiac disease (CD) and chronic liver disease (CLD) has been well described [2,3]. In this series, the mean age of patients was 28.8 years.…”
mentioning
confidence: 83%
“…In a study of liver explants, which were initially thought to be having CC, NCPF was found to be an important cause of end-stage CLD considered for liver transplantation [8]. In a recent study, NCPF was found to be associated with CD in 12 % of cases [3]. Etiology of NCPF is largely not known; however, infection and immune mechanisms may play important roles, which have also been described in the pathogenesis of CD.…”
mentioning
confidence: 99%